DISPOSAL ESTIMATION OF SUITABLE WASTE FOR RECYCLING IN RURAL AREA OF ILHA SOLTEIRA - SP - LEITE, M.A.; DORNFELD, C.B.; RENK, J.J.; SIMONATO, D.C. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The city of Ilha Solteira has several small properties and like most Brazilian rural communities face problems in the solid waste disposal. The goal of the work was to interview the owners about the presence of selective collection, the fate of waste suitable for recycling and the estimate of improperly disposed material in the rural area (Cinturão Verde, Estrela da Ilha Settlement e Santa Maria da Lagoa Settlement). The results showed that Cinturão Verde has selective collection and the plastic was the most segregated material. However, not all owners have used this service, using burning as a common practice. The settlements do not have selective collection and the incomplete burning of waste on the properties was the most used method for final disposal. It was concluded that even where there is a selective collection, its was not complete use by the owners, and the improper disposal of waste suitable for recycling occurred both in places where there is and where there is no selective collection service. This fact can cause environmental damage and public health problems in rural areas.